Penanganan fluorosis pada gigi sulung dengan menggunakan teknik mikroabrasi - Muh. Harun Achmad (Journal of Dentomaxillofacial Science, 2007)
Fluorosis is a pathological endemic effect of ion intake of flour which is more than 1ppm. Enamel fluorosis is tooth enamel demineralization due to excessive flour intakeduring tooth calcification period. Fluorosis is disparity of tooth which is initially markedwith a white line across the enamel surface, and at severe level can change tooth form.Dental fluorosis is hypoplasia or hypomaturation of tooth enamel or dentine because ofchronic usage of excessive fluor at period and development of dentition. Dental fluorosisis qualitative defect of enamel, resulted from the increase of fluor concentration at cellmicroenvironment of ameloblast during development and tooth formation. Quantitativedefect of enamel can occur on severe type of dental fluorosis. Microabrasion, consist ofair abrasion and enamel microabrasion, is a method of reducing tooth structure which isthe best alternative rather than drilling method. The mechanism of air abrasion techniqueis blast pressure of abrasive particles to remove tooth caries. The principle of kineticenergy is the abrasive particles with high pressure and speed, hit the tooth, remove toothcaries, and reduce tooth structure.